(3TQM GdcdjGJ (B-(3dGHf SjfGs - (3YdGA GdOjf Ydj Hf CHi GdMRe GdbQTi ,GdeYQha HGHf GdfajSs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdQFjS QMeg Gddg Ydjg (B: (3Gdaf GdKGdK ,aUd hNeSI JYGdje , GdaUd ai SHH GdUMI hGdeQV GdTQM (B: (3CeG PcQ SHH GdUMI hGdeQV ahLgg XGgQ hPdc dCf MaX GdUMI EfeG jcf HJMUjd CSHGHgG s
(3BNQgG (B:s
(3ajchf fbGA GdHOf efgG Chdi hYHGQI GdaUd XGgQI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs